Multifunctional nanoparticles for genetic engineering and bioimaging of natural killer (NK) cell therapeutics. (November 2019) - Kim, Kwang-Soo; Han, Jun-Hyeok; Park, Jung-Hoon; Kim, Hyung-Keun; Choi, Seung Hee; Kim, Gyeong Ryeong; Song, Haengseok; An, Hee Jung; Han, Dong Keun; Park, Wooram; Park, Kyung-Soon
Abstract: Recently, natural killer (NK)-based immunotherapy has attracted attention as a next-generation cell-based cancer treatment strategy due to its mild side effects and excellent therapeutic efficacy. Here, we describe multifunctional nanoparticles (MF-NPs) capable of genetically manipulating NK cells and tracking them in vivo through non-invasive magnetic resonance (MR) and fluorescence optical imaging. The MF-NPs were synthesized with a core-shell structure by conjugation of a cationic polymer labeled with a near-infrared (NIR) fluorescent molecule, with the aid of a polydopamine (PDA) coating layer. When administered to NKs, the MF-NPs exhibited excellent cytocompatibility, efficiently delivered genetic materials into the immune cells, and induced target protein expression. In particular, the MF-NPs could induce the expression of EGFR targeting chimeric antigen receptors (EGFR-CARs) on the NK cell surface, which improved the cells' anti-cancer cytotoxic effect both in vitro and in vivo . Finally, when NK cells labeled with MF-NPs were injected into live mice, MF-NP–labeled NK cells could be successfully imaged using fluorescence and MR imaging devices. Our findings indicate that MF-NPs have great potential for application of NK cells, as well as other types of cell therapies involving genetic engineering and in vivo monitoring of cell trafficking.